(untitled) (Research Nepal Journal of Development Studies, 2021)
Philosophically women are like goddesses but in practice, there are some misinterpretations in Nepal. Women have been designated secondary to their male counterparts, especially in the decision-making process, be it at the family level or community level, or the national/ international political context. To find out the opportunities and challenges of women in politics in Nepal, the study has selected purposively 15 leading women of Nepalese political parties. The qualitative data were collected through a semi-structured questionnaire and interview. Equity for females in the political arena has been discussed quite a lot, and in Nepal too this is a burning issue. The legal instruments, including the Constitution, have the provision for bringing in female participation in the state-level process. But the roles and participation of women in the decision-making process are considerable.